2020
DOI: 10.1002/1873-3468.13753
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of Akkermansia muciniphila peroxiredoxin reveals a novel regulatory mechanism of typical 2‐Cys Prxs by a distinct loop

Abstract: Edited by Stuart FergusonPeroxiredoxins (Prxs) are thiol-specific antioxidant proteins commonly found in organisms that protect cells from the damage of reactive oxygen species produced by metabolism and that participate in cell signaling. The Prx from the bacterium Akkermansia muciniphila (AmPrx) is a typical 2-Cys Prx characterized by two conserved cysteines: Cys49 and Cys183. Here, we verified the peroxidase activity of AmPrx and determined its crystal structure in reduced form, which is a doughnut-shaped d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…46 It was reported that A. muciniphila alleviated OS in diabetic rats 47 due to owing thiol specific antioxidant proteins such as typical 2-Cys peroxiredoxins as a family of thioredoxin (Trx)-scaffold enzymes and ubiquitous. 48 Also, Bifidobacterium longum and Lactobacillus acidophilus inhibit lipids peroxidation by scavenging ROS, 49 reducing MDA levels and increasing SOD and TAC levels. 5 Furthermore, Clostridium perfringens, probably, triggers OS by α-toxin production, and activation of mitogen-activated protein kinase/ERK kinase/extracellularsignal-regulated kinase (MEK/ERK), protein kinase C, and NF-κB pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 It was reported that A. muciniphila alleviated OS in diabetic rats 47 due to owing thiol specific antioxidant proteins such as typical 2-Cys peroxiredoxins as a family of thioredoxin (Trx)-scaffold enzymes and ubiquitous. 48 Also, Bifidobacterium longum and Lactobacillus acidophilus inhibit lipids peroxidation by scavenging ROS, 49 reducing MDA levels and increasing SOD and TAC levels. 5 Furthermore, Clostridium perfringens, probably, triggers OS by α-toxin production, and activation of mitogen-activated protein kinase/ERK kinase/extracellularsignal-regulated kinase (MEK/ERK), protein kinase C, and NF-κB pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Costantini et al reported that OM3FA intake stimulated the growth of A. muciniphila , Bifidobacteria , Lactobacilli , Faecalibacterium , Roseburia , and inhibited some pathogenic bacteria, such as the Enterobacteriaceae , Clostridium , and Streptococcus 46 . It was reported that A. muciniphila alleviated OS in diabetic rats 47 due to owing thiol specific antioxidant proteins such as typical 2‐Cys peroxiredoxins as a family of thioredoxin (Trx)‐scaffold enzymes and ubiquitous 48 . Also, Bifidobacterium longum and Lactobacillus acidophilus inhibit lipids peroxidation by scavenging ROS, 49 reducing MDA levels and increasing SOD and TAC levels 5 .…”
Section: Discussionmentioning
confidence: 99%
“…49 It was reported that A. muciniphila alleviated OS in diabetic rats 50 due to having thiol specific antioxidant proteins such as typical 2-Cys Peroxiredoxins as a family of thioredoxin (Trx)-scaffold enzymes and ubiquitous. 51 Bifidobacterium longum and Lactobacillus acidophilus inhibited lipids peroxidation by scavenging ROS 52 , reducing MDA levels and increasing SOD and TAC levels. 5 Also, Clostridium perfringens, probably, triggers OS by α-toxin production, and activation of mitogen-activated protein kinase/ERK kinase/extracellular-signal-regulated kinase (MEK/ERK), protein kinase C, and NF-κB pathways.…”
Section: Discussionmentioning
confidence: 99%